Economicalness of self-propelled work platforms in superintensive apple plantations - Szabó, Viktor (Acta Agraria Debreceniensis, 2016)
The main goal of this study was to determine whether the use of work platforms in super intensive apple orchards in order to reduce production costs and enhance work area performance under Hungarian circumstances an economic investment is. The analysis was carried out using a deterministic simulation model based on primary data collection from apple producing businesses. The results show that work platforms have remarkable economic advantage in case of operations with high machine work expenditures or where they significantly improve the area performance of manual labour. The former was due to the much lower operating costs of work platforms compared to tractors, while the latter comes clear from reduction of manual labour input per hectare. The greatest economic advantage of work platforms occurs in case of harvesting and pruning, but in case of other operations they have no significant cost advantage. They main economic disadvantage is, however, that apple breaks more when harvesting with work platforms, i.e. picking quality deteriorates significantly. It can be concluded, that purchase of work platforms cannot be considered economic investment under Hungarian circumstances. It might be economic, utilised on maximum area (ca. 30 hectares) by certain companies in special cases, but in most cases has no favourable payback conditions.